2017
DOI: 10.5586/asbp.3525
|View full text |Cite
|
Sign up to set email alerts
|

Production and antioxidant capacity of tissue cultures from four Amaryllidaceae species

Abstract: The aim of this study was (i) to produce tissue cultures capable of efficient plant regeneration from European naturally occurring protected and/or pharmacologically important Amaryllidaceae species and (ii) to test them for antioxidant activities in order to select tissue cultures that scavenge efficiently oxygen radicals. Bulb explants were collected from Galanthus woronowii, two Leucojum species, and Sternbergia lutea. Leucojum species were Hungarian isolates. Mostly α-naphthalene acetic acid (NAA) and benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Therefore, O. vulgare can be considered as a species very rich in polyphenols. [61][62][63][64] On the other hand, when we compare the TPC value of the gold colloids with the value of pure extracts, for the same amount of DW, it appears that the TPC of colloids is ~3.5 times smaller. This striking difference might be due to the fact that, at least partially, the polyphenols were "consumed" during the synthesis of gold colloids.…”
Section: Polyphenolic Content and Radical Scavenging Activitymentioning
confidence: 99%
“…Therefore, O. vulgare can be considered as a species very rich in polyphenols. [61][62][63][64] On the other hand, when we compare the TPC value of the gold colloids with the value of pure extracts, for the same amount of DW, it appears that the TPC of colloids is ~3.5 times smaller. This striking difference might be due to the fact that, at least partially, the polyphenols were "consumed" during the synthesis of gold colloids.…”
Section: Polyphenolic Content and Radical Scavenging Activitymentioning
confidence: 99%
“…Narcissus bulbs are the main source for alkaloid extraction and some cultivars and species contained more than 0.1% (DW basis) of galanthamine in their bulbs [16]. In vitro tissue and tissue-based systems have been proposed for commercial applications such as production of metabolites and clonal propagation [17,18]. Undifferentiated callus or suspension cultures have been mainly used for the production of alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Auxins and cytokinins play major roles by either blocking or stimulating outgrowth, respectively (Shahin et al, 2018). It has been reported that different combinations of these PGRs have the potential of callus induction or micropropagation in this plant family (Resetár et al, 2017). Ivanov et al (2011) used 1.15 mg L -1 NAA and 2 mg L -1 BA for callus induction in L. aestivum plant.…”
Section: Introductionmentioning
confidence: 99%